Central pain due to spinothalamic tract injury caused by indirect head trauma following a pratfall. (6th June 2016) - Jang, Sung Ho; Lee, Han Do
Abstract: Objectives : This study reports on patients who showed central pain due to injury of the spinothalamic tract (STT) caused by fall without direct head trauma. Design : Prospective study. Participants : Two patients with mild traumatic brain injury (TBI) resulting from a fall were enrolled. Patient 1 was a 21-year-old female who had suffered a pratfall with no history of direct head trauma. She had begun to feel pain in both upper trunk and lower back and the left leg since 5 days after onset: constant tingling and throbbing sensation with allodynia. Patient 2 was a 39-year-old male who had suffered a pratfall without direct head trauma. He had begun to feel pain in both arms and legs since 4 days after the fall: constant tingling and pricking sensation without allodynia or hyperalgesia. Results : On diffusion tensor tractograhpy (DTT) of patient 1, partial tearing of the right STT was observed at the subcortical white matter. On DTT of patient 2, partial tearing at the subcortical white matter was observed in the right STT and partial narrowing at the subcortical white matter was observed in the left STT. Conclusions : This study demonstrated injury of the STT in patients who suffered from central pain following a fall. The results suggest that minor indirect head trauma can cause traumatic axonal injury of the brain.